Liver Cancer Genesis, Progression and Metastasis - Feitelson, Mark; Arzumanyan, Alla (IntechOpen, 2023)
Hepatocellular carcinoma (HCC) is a common tumor type arising from several distinct etiologies. It is usually diagnosed late and is difficult to treat. This volume presents an overview of selected aspects of HCC pathogenesis, and research aimed at developing diagnostic biomarkers. It points to a number of putative therapeutic targets, including signal transduction pathways, metabolic and epigenetic alterations in tumor cells, the tumor microenvironment, the gut microbiome, and functions of immune effector cells. Given the multi-step nature of most cancers, including HCC, future drug development will most likely require combination therapies that will simultaneously target multiple steps in hepatocarcinogenesis.